2021
DOI: 10.1101/2021.12.30.474462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolution and biological correlates of hand preferences in anthropoid primates

Abstract: The evolution of human right-handedness has been intensively debated for decades. Manual lateralization patterns in non-human primates have the potential to elucidate evolutionary determinants of human handedness. However, restricted species samples and inconsistent methodologies are limiting comparative phylogenetic studies. By combining original data with published literature reports, we assembled data on hand preferences for standardized object manipulation in 1,806 individuals from 38 species of anthropoid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Meguerditchian et al [414], in an analysis similar to that for marsupials, found that ecology rather than phylogeny seemed important, arboreal species showing a left-hand preference for bimanual coordinated tasks, whereas terrestrial species tended to be right-handed. The more extensive study of 38 species of anthropoid primates by Caspar et al [415] found little phylogenetic influence on direction of handedness, suggesting "unique selective pressures gave rise to . .…”
Section: The Evolution Of Heart Asymmetry and Brain Asymmetrymentioning
confidence: 99%
“…Meguerditchian et al [414], in an analysis similar to that for marsupials, found that ecology rather than phylogeny seemed important, arboreal species showing a left-hand preference for bimanual coordinated tasks, whereas terrestrial species tended to be right-handed. The more extensive study of 38 species of anthropoid primates by Caspar et al [415] found little phylogenetic influence on direction of handedness, suggesting "unique selective pressures gave rise to . .…”
Section: The Evolution Of Heart Asymmetry and Brain Asymmetrymentioning
confidence: 99%
“…Firstly, this study reviews the state of the art of manual laterality studies in non-human primates with those tasks (coordinated bimanual actions) that are potentially more sensitive and precise for measuring manual preferences. To date, we have not found any published review or meta-analysis comparable to this one, except for a recent pre-print that includes some of our database and incorporates new data not included in the present meta-analysis (Caspar et al, 2021). Secondly, it highlights the great heterogeneity of procedures, assessments and sample sizes used in laterality research in nonhuman primates.…”
Section: Discussionmentioning
confidence: 96%
“…It would be especially relevant in future studies to test whether hand preference is linked to phylogeny and species-level predictors (e.g. vocal repertoire, dietary breadth, group size, terrestriality, home range or feeding budget) through phylogenetic analysis (Caspar et al, 2021). That is, to identify the possible factors that drive or influence this trait along the phylogenetic tree.…”
Section: Evolutionary Significance Of Individual and Population-level...mentioning
confidence: 99%
“…Yet, population-level handedness (i.e. the tendency of the majority of the population toward using a specific hand as is known in humans) is extremely rare in animals [ 17 ]. Instead, vast individual variation in direction (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…asymmetry in hemispheric functions, has been hypothesized as one of the possible proximate neurophysiological mechanisms that maintain personality variation [12,13]. Brain lateralization is expressed as a preference for using the contralateral part of the body and is often measured either as a limb preference [14][15][16][17][18], eye dominance [19,20] or tail and body orientation [12,21,22]. Brain lateralization is present both in vertebrates and invertebrates (reviewed in [23,24]), and it provides various benefits in terms of enhanced cognition, social cohesion and better predator detection while foraging [25][26][27], thus directly affecting an individual's survival.…”
Section: Introductionmentioning
confidence: 99%